Ultrasound mapping of new cannulation sites for arteriovenous fistulas/grafts at South Tyneside and Sunderland NHS Foundation Trust (STSFT) Renal Unit. - Ayub, Haroon; Clark, Rauri; Srivastava, Shalabh; Andrews, James; Sweeney, Debra; Ahmed, Saeed (Pakistan Journal of Kidney Diseases, 2021)
The cannulation of vascular access specially becomes difficult in elderly, diabetic and obese hemodialysis patients. The accessibility of an AV fistula largely relies on the condition of the patient’s veins, which often leads to difficulty in cannulation with the traditional blind method. South Tyneside and Sunderland NHS Foundation Trust (STSFT) Renal unit adopted ultrasound mapping of new cannulation sites for arteriovenous fistulas and arteriovenous grafts. The aim of this study was to evaluate the qualitative impact of this practice on the dialysis patients. This was a qualitative study and was conducted in the Renal Unit at STSFT. Haemodialysis patients with deep or small vessels for cannulation, a vessel with problems and a vessel whose cannulation on the first attempt was vital were included in the study. AVF/AVG were mapped using Doppler ultrasound (US) undertaken by a consultant Interventional Nephrologist (IN). The map of the AVF/AVG and new cannulation sites were captured as an image on the patients’ smart phone to act as record to show the dialysis nurse cannulating the AVF/AVG. It was hoped that this would encourage rope laddering and AVF/AVG preservation. Patients reported no significant improvement in cannulation process even after US mapping of new cannulation sites. Patients did report a better understanding of the AVF/AVG geometry especially amongst the self cannulators on home haemodialysis. According to the patients the successful cannulation was mainly dependent on the skills of dialysis nurses rather than the US mapping of the AVF/AVG being of any assistance.